Digitalisasi Promosi dan Manajemen UMKM untuk Penguatan Identitas Desa Tanggilingo sebagai Desa Kreatif - Rampi Yusuf; Rahmat Taufik R.L Bau; Salahudin Olii; Zulhair Jidan S. Tamu; Syakir Alhasni; Muhammad Surya Ramadhan Nompo (Universitas Negeri Gorontalo, 2026)
Digital transformation has become an essential requirement for micro, small, and medium enterprises (MSMEs) to enhance their competitiveness and business sustainability. However, most MSMEs in Tanggilingo Village, Bone Bolango Regency, continue to face several challenges, including limited adoption of digital technologies, inadequate product visual identity, and reliance on manual administrative management. This community service program aimed to strengthen Tanggilingo Village’s identity as a creative village through the digitalization of promotion and management practices among home-based MSMEs. The program employed a participatory approach consisting of MSME needs assessment, AI-based product rebranding training, content curation and digitalization, development of a Point of Sales (POS)-based platform, and user acceptance evaluation of the developed system. The results showed that 30 MSMEs were engaged in the program. The rebranding training resulted in the creation of 26 new logo designs and four alternative packaging designs, while the content curation process successfully documented all participating products and business profiles. Furthermore, the developed digital platform effectively accommodated the partners’ needs related to transaction recording, product management, inventory control, business reporting, and digital promotion. User evaluation demonstrated a high level of acceptance, with average scores of 90% for ease of use, 92% for perceived usefulness, and 95% for user satisfaction. The program contributed positively to improving digital capacity, strengthening product identity, and promoting more structured business management practices. Moreover, the integrated digital platform has the potential to support the development of a local MSME ecosystem and reinforce Tanggilingo Village’s identity as a creative village driven by local economic potential.